P-078 A Survey of Gastroenterologists' Understanding of Therapeutic Drug Monitoring in IBD Patients: Is There Room for Improvement?. (February 2017) - Szeto, Winnie; Moss, Alan C.; Farraye, Francis
Abstract : Background: Therapeutic drug monitoring (TDM) has been advocated as a diagnostic technique to improve outcomes in patients with IBD. Little is known if gastroenterologists interpret TDM results correctly. In this study, we describe gastroenterologists' interpretation and response to 3 different clinical scenarios which included TDM results. Methods: We emailed an 8 question online survey to gastroenterologists who are members of the American College of Gastroenterology using Survey Monkey from January 2016 to May 2016. Respondents demographics were obtained including practice setting (academic or private practice), average number of IBD patients seen in a week (<5, 5–10, 11–20, 20+), age of the participant, and attendance at major gastroenterology conferences (DDW, CCFA, ECCO, ACG). Three IBD clinical case scenarios were provided with TDM results and a single multiple choice question to answer. Results: The survey was sent to 5879 gastroenterologists; 1687 opened the email (29%), and 143 completed the survey (8%). Of the respondents, 49% practice in academic medical centers and 43% in private practice. Thirty-eight percent of the participants see 5 to 10 IBD patients a week and 18% see 20 or more patients a week. The participants ages were 20 to 39 (41%), 40 to 59 (43%) or older than 60 (16%). Participants attended the ACG annual meeting (45%), CCFA annual meeting (45%), DDW (55%) and/or ECCO (3%) within the past year. In the scenario of a symptomatic patient with loss of response due to low trough levels and high anti-drug antibodies, 63% of respondents would switch within anti-TNF class, but 23% would increase the dose of the anti-TNF. In the case of a symptomatic patient with loss of response despite adequate drug levels with no anti-drug antibodies, 9% would increase the dose and 37% would add a thiopurine. Finally, in the scenario of a primary non-responder to a single 10 mg/kg infliximab dose in an inpatient with severe steroid-refractory ulcerative colitis, 21% would give an additional 10 mg/kg dose 3 days after the initial dose while 43% of gastroenterologists would give an additional dose in 2 weeks. Conclusions: Our study demonstrates that there are wide variations in response to TDM results in the described clinical practice scenarios. A substantial proportion (23%) of gastroenterologists would increase the dose of anti-TNF in symptomatic patients with high anti-drug antibody levels. Despite therapeutic trough levels and no anti-drug antibodies in a symptomatic patient, 9% of respondents would increase the drug dose or add a thiopurine (37%). An accelerated infliximab induction regimen is not widely utilitzed in cases of hospitalized severe steroid-refractory ulcerative colitis. Interpretation of therapeutic drug monitoring results can be challenging in specific clinical scenarios. Therefore, additional efforts are needed to educate gastroenterologists on the interpretation of therapeutic drug monitoring results in order to optimize the use of anti-TNFs and improve outcomes.